Impact of rural agricultural work experience (RAWE) programe on agriculture graduates of Vellayani campus, KAU - Shifa Dhas Y (Department of Agricultural Extension, College of Agriculture, 2006)
The study entitled ‘Impact of Rural Agricultural Work Experience (RAWE) programme on agriculture graduates of Vellayani campus, KAU’ was undertaken to assess the impact of RAWEP in empowering the B.Sc. Agriculture graduates, their profile characters and their relationship with empowerment. The study also aimed to analyse the strengths, weaknesses, opportunities and threats of the programme, identify the constraints and make suggestions for improving RAWEP.